What does internationalisation or interculturalisation look like in the future in the higher education sector? - Bennett, Dawn; Hartwig, K.; Barton, G.; Ferns, S.; Joseph, D.; Podorova, A.; Jones, L.; Cain, M.; Campbell, M.; Tangen, D.; Westerveld, M.; Larkin, I.; et al. (Springer, 2017)
What is internationalisation? What is interculturalization? What will these concepts look like in the future? Will they exist or move beyond their current state? Where are universities/higher education institutions headed with their international strategies as they prepare global citizens for the future? How will universities of the future cater for international students? These are the questions considered in this final chapter. This chapter contains reflections from the team members. We begin by defining internationalization and interculturalization in relation to employability. This is followed with reflections on the project as it was experienced within the six participating universities. We then bring together the reflections to highlight the key themes, which inform recommendations for practice and for future research.